Mutation of arginine residues to avoid non-specific cellular uptakes for hepatitis B virus core particles - Mohamed Suffian, Izzat Fahimuddin; Nishimura, Yuya; Morita, Kenta; Nakamura-Tsuruta, Sachiko; Al-Jamal, Khuloud; Ishii, Jun; Ogino, Chiaki; Kondo, Akihiko (Biomed Central, 2015)
BACKGROUND: The hepatitis B virus core (HBc) particle is known as a promising new carrier for the delivery of drugs and nucleic acids. However, since the arginine-rich domain that is located in the C-terminal region of the HBc monomer binds to the heparan sulphate proteoglycan on the cell surface due to its positive charge, HBc particles are introduced non-specifically into a wide range of cells. To avoid non-specific cellular uptake with the intent to control the ability of cell targeting, we individually replaced the respective arginine (R) residues of the arginine-rich domain located in amino acid positions 150-159 in glycine (G) residues. RESULTS: The mutated HBc particles in which R154 was replaced with glycine (G) residue (R154G) showed a drastic decrease in the ability to bind to the heparan sulphate proteoglycan and to avoid non-specific cellular uptake by several types of cancer cells. CONCLUSIONS: Because this mutant particle retains most of its C-terminal arginine-rich residues, it would be useful in the targeting of specificity-altered HBc particles in the delivery of nucleic acids.